Entrepreneurial intention among university students in Malaysia: integrating self-determination theory and the theory of planned behavior - Al-Jubari, Ibrahim; Hassan, Arif; Liñán, Francisco (Springer Nature, 2018)
The present study endeavors to develop a deeper understanding of the motivational processes involved in intentional entrepreneurial behavior. For this purpose, it integrates the social cognitive approach of the theory of planned behavior (TPB) and the organismic theory of motivation of self-determination theory (SDT). More specifically, it tests the role of basic psychological needs of autonomy, competence and relatedness as defined in SDT in shaping university students’ attitudes and intentions toward entrepreneurship. The sample of this study consisted of 438 (Males = 166, Females =272) 3rd and 4th year university students from four Malaysian Public Universities. The results of the study show that the model strongly explains about 71% of the variance in entrepreneurial intention. Basic psychological needs of autonomy, competence and relatedness have a strong indirect impact on entrepreneurial intention via their attitudinal antecedents: attitude, subjective norm, and perceived behavioral control. This indicates a full-mediational model, where the attitudinal factors operated as transmitters of effects from the distal constructs of SDT on entrepreneurial intention. These findings confirm that both SDT and the TPB provide complementary explanations of the motivational processes of entrepreneurial behavior. The study contributes to the existing knowledge by providing a theory-based understanding of the role of motivations in the formation of entrepreneurial intentions. It opens the way for future research to analyze how alternative motivations may affect new venture creation, survival and success.